Patterns and Predictors of Cyber Delinquency among Minors in the Internet Era (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research article delves deep in analysis of emerging patterns of internet related offenses committed by minors along with multi-dimensional aspects of internet society which has created a cyber-world. Our global world is continuously transforming with the everyday use of internet technologies which are playing significant role in transforming the human society. This change is multifaceted, driven by the advent of ‘Information and Communication Technologies (ICT) that was widely being used since 20th century and have rapidly advanced in the present era. ICT involves the digital transmission of data between various devices worldwide. “Information technology is the "the science and activity of moving data digitally. (Gutmann, 2001)” Emerging society is an "information society." (Castells & Gustavo, 2005) Internet technology and social media are the most prominent and revolutionary innovations, bringing remarkable changes to modern society creating cyber-cultures. In context of Indian society which is facing numerous modern challenges and issues and is evolving into a "risk society," as it transitions "from etiquettes to netiquettes, from school bullying to cyberbullying, from theft to cyber-fraud, multiple new aspects of deviance and crimes are evolving" The internet and social media have created a cyber-world through social networking, forming a network society where data is sensitive and preciousInternet and social media are now inalienable part of human lives, having both positive and negative impact on minors especially. Internet is the fastest and cheapest means through which data can be transmitted in real time at any place on globe but on the other hand, they also expose users especially minors to risks being a cyber-delinquent but also a victim of cyber-crimes. Since the evolution of human society crime has always been an integral part of human society, but with the expansion of the internet and social media, its patterns and methods are continuously evolving. Delinquency is now becoming cyber-delinquency with the involvement of internet technology. This study is based on qualitative analysis of Patterns and Predictors of Cyber Delinquencies committed by minors and how effects society it when committed by minors. This study relies on primary data being sourced from various stake-holders of judiciary, academia and member of civil society, students and victim of cyber-crimes while secondary data is sourced from NCRB and government records and official academic data from journals and books.